Pelatihan Masyarakat Lingkar Kampus: Kualitas dan Kuantitas Telur Burung Puyuh Yang Mengalami Cekaman - Koekoeh Santoso; Athirah Rerana Fitrianthy; Aryani Sismin Satyaningtijas; Damiana Rita Ekastuti; Isdoni Isdoni; Maharani Salsabila (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Global warming has caused heat stress in quail (Coturnix coturnix Japonica). Heat stress can cause an increase in free radicals, through increased production and secretion of glucocorticoid hormones, which exceed the ability of the body's antioxidant system, causing oxidation, especially of double bonded lipid compounds found in cell membranes. Long-term secretion of glucocorticoids can cause a decrease in reproductive function. Dexamethasone is a glucocorticoid drug. The purpose of this study was to determine the effect of giving dexamethasone, as an analogy to glucocorticoid secretion in quail, on the quantity and quality of eggs produced by quail. Egg quality observed was length, width, weight, yolk weight and percentage, Haugh unit, white weight and percent, white height, egg shell weight and thickness. This study used 16 quails which were divided into four groups, namely one control group and three dexamethasone groups. The doses of dexamethasone given were 1.25 mg/kg BW, 2.5 mg/kg BW, and 5 mg/kg BW. Dexamethasone was given orally for two weeks. Sampling was carried out every day since the start of the study. The results showed that the administration of dexamethasone caused a decrease in the quantity and quality of eggs produced by quail.